Facial thirds–based evaluation of facial asymmetry using stereophotogrammetric devices: Application to facial palsy subjects. Issue 1 (January 2017) - Codari, Marina; Pucciarelli, Valentina; Stangoni, Fabiano; Zago, Matteo; Tarabbia, Filippo; Biglioli, Federico; Sforza, Chiarella
Abstract: Many conditions can compromise facial symmetry, resulting in an impairment of the affected person from both esthetic and functional points of view. For these reasons, a detailed, focused, and objective evaluation of facial asymmetry is needed, both for surgical planning and for treatment evaluation. In this study, we present a new quantitative method to assess symmetry in different facial thirds, objectively defined on the territories of distribution of trigeminal branches. A total of 70 subjects (40 healthy controls and 30 patients with unilateral facial palsy) participated. A stereophotogrammetric system and the level of asymmetry of the subjects' hemi-facial thirds was evaluated, comparing the root mean square of the distances (RMSD) between their original and mirrored facial surfaces. Results show a high average reproducibility of area selection (98.8%) and significant differences in RMSD values between controls and patients (p = 0.000) for all of the facial thirds. No significant differences were found on different thirds among controls (p > 0.05), whereas significant differences were found for the upper, middle, and lower thirds of patients (p = 0.000). The presented method provides an accurate, reproducible, and local facial symmetry analysis that can be used for different conditions, especially when only part of the face is asymmetric.